UiO-66-X ammonia adsorption material as well as preparation method and application thereof

The UiO-66-X material was prepared by using a formic acid-ethanol-water ternary solvent system and a segmented temperature-controlled hydrothermal method, which solved the problems of zirconium-based MOFs materials being easily hydrolyzed in high humidity environments and having poor adsorption effects at low temperatures and low pressures. It achieved high stability and efficient ammonia adsorption, reducing the risk of environmental pollution.

CN120795338APending Publication Date: 2025-10-17KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511007830.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing zirconium-based MOFs materials are easily hydrolyzed and structurally collapsed in high-humidity environments, and their adsorption effect on ammonia is not ideal at low temperature and low pressure. The traditional solvent DMF is harmful to the environment and health. Existing technologies make it difficult to prepare zirconium-based MOFs materials with high stability, large specific surface area and good selectivity.

Method used

The UiO-66-X material was prepared using a formic acid-ethanol-water ternary solvent system and a segmented temperature-controlled hydrothermal method. By synergistically regulating the coordination environment and surface groups of the zirconium clusters, a stable Zr6O4(OH)4 core was formed, thereby improving the water stability and ammonia adsorption performance of the material.

Benefits of technology

The adsorption capacity and selectivity of ammonia are significantly improved at low temperature and low pressure. The material structure is highly stable, the risk of solvent pollution to the environment is reduced, and an efficient ammonia adsorption and desorption process is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795338A_ABST
    Figure CN120795338A_ABST
Patent Text Reader

Abstract

The invention discloses a UiO-66-X ammonia adsorption material as well as a preparation method and application thereof, and belongs to the technical field of metal organic framework materials (MOFs). By means of a formic acid-ethanol-water ternary solvent coordinated regulation strategy and a segmented temperature control method, controllable defects and surface functional groups are introduced into a UiO-66 skeleton, the adsorption capacity of the material to NH3 under 298 K / 1 bar reaches 11.1 mmol / g, and the structural integrity retention rate gt after 30 days of water immersion is achieved; and high-efficiency desorption can be realized at the temperature of 80 DEG C. The material is suitable for efficient adsorption and resource recovery of ammonia in high-humidity and high-sulfur industrial waste gas, and has remarkable economic and environment-friendly values.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of metal organic framework materials (MOFs), and particularly relates to a UiO-66-X ammonia adsorption material and a preparation method and application thereof. BACKGROUND

[0002] As a typical pollutant, ammonia often exists in urban and industrial wastewater, and its concentration varies depending on the source. In industrial wastewater, the concentration of ammonia is usually between 5 and 1000 mg / L, and the main sources include the production of chemical fertilizers, coking plants, pharmaceuticals, petroleum refining, coal gasification, and catalyst manufacturing industries. The ammonia content in municipal wastewater is usually in the range of 10 to 200 mg / L. Long-term exposure to ammonia has a wide range of adverse effects on the environment and living organisms. Excessive ammonia in the environment can accelerate the eutrophication of rivers and lakes, i.e., the accumulation of nutrients such as nitrogen and phosphorus in water bodies, ultimately leading to the depletion of dissolved oxygen in water bodies, causing toxic effects on aquatic ecosystems, especially on fish and other aquatic organisms. In addition, ammonia can cause a series of physiological changes, including changes in cell pH, depletion of citric acid cycle intermediates, and neurotransmitter disorders. This ammonia poisoning can cause fish to exhibit hyperactivity and convulsions, and in severe cases, can lead to lethargy, loss of balance, and eventually coma. From the perspective of human health, inhaling ammonia can directly cause a series of respiratory system diseases, such as tracheobronchitis, bronchiolar inflammation, laryngitis, bronchopneumonia, and pulmonary edema. In acute poisoning survivors, long-term exposure can also lead to serious health problems such as chronic obstructive pulmonary disease or interstitial lung disease.

[0003] However, MOFs prepared by traditional solvothermal method are prone to hydrolysis in high humidity environment, leading to structural collapse. The microporous structure is single, lacking open metal sites and functional groups, and the adsorption efficiency for low concentration ammonia is insufficient. Zirconium-based MOFs materials are most widely used due to their high water stability, and are considered as a promising material for industrial sites due to their special robustness. However, the preparation of zirconium-based MOFs materials currently uses N,N'-dimethylformamide (DMF) solvent, but DMF has high solubility in water, and once leaked into water, it will have toxic effects on aquatic organisms and gradually accumulate through the food chain, affecting the balance of the ecosystem. Moreover, DMF has strong volatility, and when it escapes into the air, it will have a negative impact on air quality, especially in closed or poorly ventilated environments, which can easily lead to high DMF concentration in the air, posing a threat to the health of surrounding personnel. Furthermore, the zirconium-based MOFs materials prepared by the existing technology have improved adsorption effect on ammonia gas at normal temperature and pressure, but the adsorption effect on ammonia gas at low temperature and low pressure is not ideal. Therefore, it is necessary to explore a more environmentally friendly preparation method for zirconium-based MOFs materials, and the prepared zirconium-based MOFs materials should have high stability, high specific surface area, good selectivity, and good ammonia gas adsorption capacity at low temperature and low pressure. SUMMARY

[0004] In order to overcome the above-mentioned defects of the prior art, the present application provides a UiO-66-X material with high water stability, high ammonia adsorption capacity and selectivity, and low desorption energy consumption, and a preparation method thereof, wherein the target product is prepared by a preparation segmented temperature control hydrothermal method in combination with a formic acid-ethanol-water ternary solvent system synergistic regulation strategy, thereby breaking through the technical bottleneck of traditional MOFs in industrial waste gas treatment.

[0005] To achieve the above-mentioned purpose, the technical scheme adopted by the present application is as follows:

[0006] A preparation method of a UiO-66-X ammonia adsorption material, comprising the following steps: mixing a zirconium salt and an organic ligand, and then adding to a formic acid, ethanol and water ternary solvent for hydrothermal reaction; after the reaction is completed, cooling to room temperature, separating, washing and drying to obtain a UiO-66-X material for ammonia adsorption; the chemical formula of the UiO-66-X material for ammonia adsorption is Zr6O4(OH)4(X) 6-n (COOH) n , wherein X is a terephthalic acid derivative, and n=1-3.

[0007] The present application synergistically regulates the coordination environment and surface groups of the UiO-66-X material by formic acid, ethanol and water, improves the ammonia adsorption capacity of the UiO-66-X material, and improves the material structure and ammonia adsorption performance stability, and has high selectivity for ammonia, especially the ammonia adsorption capacity is greatly improved at low temperature and low pressure.

[0008] The present application also explores that the formic acid is replaced by benzoic acid, and due to the difficulty in effectively adjusting the zirconium cluster coordination, the ammonia adsorption capacity of the finally prepared material is significantly reduced to below 4mmol / g; if the ethanol is replaced by methanol, the methanol competes with the formic acid for coordination, resulting in collapse of the material pore structure, and the ammonia adsorption capacity of the finally prepared material is significantly reduced to below 4mmol / g.

[0009] As a preferred embodiment of the present application, the zirconium salt is one of zirconium tetrachloride, zirconium octahydrate oxychloride, zirconium nitrate oxyhydrate, zirconium tetraacetate, and zirconium acetate hydrate.

[0010] As a preferred embodiment of the present application, the organic ligand is one of 2-amino terephthalic acid, 2-hydroxy terephthalic acid, 2-methyl terephthalic acid, 2-trifluoromethyl terephthalic acid, 2-chloro terephthalic acid, 2-fluoro terephthalic acid, 2-bromo terephthalic acid, 2-iodo terephthalic acid, 2,5-dichloro terephthalic acid, 2,6-dichloro terephthalic acid, 2,5-difluoro terephthalic acid, 2,3-difluoro terephthalic acid, tetrafluoro terephthalic acid, 2-bromo-5-fluoro terephthalic acid, 2,5-dibromo terephthalic acid, tetrabromo terephthalic acid, 2,5-dihydroxy terephthalic acid, and 2,5-diiodo terephthalic acid.

[0011] As a preferred embodiment of the present application, the temperature of the hydrothermal reaction is 120-150℃, and the time is 20-24h.

[0012] More preferably, the hydrothermal reaction adopts segmented temperature control, specifically: the first stage is heated to 120℃ for 4h, and the second stage is heated to 150℃ at a rate of 3℃ / min and kept for 18h.

[0013] As a preferred embodiment of the present application, the molar ratio of the organic ligand and the zirconium salt is 1:(0.8-1.2).

[0014] As a preferred embodiment of the present application, the molar ratio of the zirconium salt and formic acid is 1:(1-2). When formic acid is in excess, it will preferentially bind to zirconium ions (Zr 4+ ) to occupy coordination sites, hindering the coordination of the organic ligand (such as 2-amino terephthalic acid) with the zirconium cluster, resulting in incomplete UiO-66 framework structure and affecting the ammonia adsorption capacity.

[0015] As a preferred embodiment of the present application, the volume ratio of formic acid, ethanol and water is 1:(2-4):2-3.

[0016] If the volume ratio of formic acid, ethanol and water is not within the range defined in the present application, the adsorption capacity of the prepared material is about 4mmol / g or even lower than 4mmol / g.

[0017] The present application also claims the UiO-66-X material prepared by the method for preparing the UiO-66-X ammonia adsorption material.

[0018] The present application also claims the application of the UiO-66-X material in NH3 adsorption.

[0019] Compared with the prior art, the present application has the beneficial effects that: the present application uses zirconium salt and organic ligand as raw materials, formic acid, ethanol and water as solvents, and a preparation method combining segmented temperature control to prepare the UiO-66-X material, and in the segmented temperature control process, the formic acid, ethanol and water are used to cooperatively regulate the coordination environment and surface groups of the UiO-66-X material, which is helpful to form a complete Zr6O4(OH)4 core, and the coordination environment is stable, and the water stability of the UiO-66-X material is not affected, and the ammonia adsorption amount of the UiO-66-X material under low pressure is improved, and the material structure and ammonia adsorption performance stability are improved, and the selectivity for ammonia is high. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 is the XRD graph of the material prepared in Example 1 and Comparative Example 1-2 before and after adsorbing ammonia.

[0021] Figure 2 is the comparison graph of the ammonia adsorption effect of the material prepared in Example 1 before and after soaking in water for 30 days.

[0022] Figure 3 is the FTIR graph of the material prepared in Example 1-3 and UiO-66. DETAILED DESCRIPTION

[0023] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in combination with specific examples.

[0024] Example 1

[0025] A preparation method of a UIO-66-NH2 ammonia adsorption material, comprising the following steps: dissolving 1 mmol of ZrCl4 and 1 mmol of 2-amino terephthalic acid in 45 mL of a mixed solvent (formic acid:ethanol:water = 1:3:2), transferring the solution into a polyethylene-lined reaction kettle, heating to 120℃ at a rate of 3℃ / min and keeping for 4 hours, and then heating to 150℃ at a rate of 3℃ / min in the second stage and keeping for 18 hours. After the reaction is completed, cool to room temperature, collect the product by centrifugation, wash with ethanol and deionized water for 3 times in turn, filter, and vacuum dry the obtained filter cake at 60℃ for 12h to obtain a light yellow MOFs material UIO-66-NH2 containing amino ligand.

[0026] From Figure 1It can be seen that the peak positions of the XRD patterns of Example 1 before and after adsorption are almost identical, indicating that the synthesized UIO-66-NH2 material remains stable in structure during the adsorption process, without obvious framework collapse or crystal phase transition, and still has good crystallinity. The diffraction peaks in the pattern are sharp and clear, corresponding to the ideal crystal structure. This high stability is attributed to the multi-solvent system regulation strategy adopted during synthesis. Ethanol (weak polarity) and water (strong polarity) together provide a variable dielectric environment, which helps to adjust the solubility and crystal growth rate; at the same time, formic acid as a regulator can compete with Zr 4+ for coordination, inhibiting the rapid crystallization process, thereby effectively reducing the generation of structural defects.

[0027] In contrast, the XRD pattern of Comparative Example 1 shows a slight shift in peak position between before and after adsorption, indicating that its structure has undergone a certain degree of instability or defect formation during the adsorption process. The diffraction peaks in its pattern are relatively broad, and the crystallinity is slightly inferior to that of Example 1, and there may be local framework deformation or slight dissociation after adsorption. DMF, a strong polar solvent, was used in the synthesis of this material, which can quickly dissolve the precursor, facilitating crystal nucleation, but also easily accelerating crystal growth. However, DMF competes for Zr sites, leading to incomplete coordination or the formation of byproducts (non-MOF structure precipitates), resulting in a large number of structural defects, which in turn triggers local damage to the framework during the adsorption process, reflected in the changes in the XRD pattern.

[0028] For Comparative Example 2, the change in its pre-adsorption and post-adsorption pattern is more dramatic, with some peak positions being blurred or disappearing, indicating that the material's structure was significantly damaged or even collapsed during the adsorption process. This phenomenon is mainly due to the addition of concentrated hydrochloric acid during synthesis, which significantly changes the coordination process of the precursor, weakening its coordination ability with Zr 4+ . At the same time, Cl-ions compete with Zr 4+ for coordination, further interfering with the ordered construction of the UIO-66-NH2 structure, ultimately leading to poor crystallinity and many defects in the material, resulting in instability during the adsorption process.

[0029] Example 2

[0030] A method for preparing a UIO-66-OH ammonia adsorption material, comprising the following steps: dissolving 1 mmol of ZrCl4 and 1 mmol of 2-hydroxyterephthalic acid in 45 mL of a mixed solvent (formic acid: ethanol: water = 1:3:2), transferring the solution into a polyethylene-lined reaction kettle, heating to 120°C at a rate of 3°C / min and maintaining for 4 hours, and then heating to 150°C at a rate of 3°C / min in the second stage and maintaining for 18 hours. After the reaction is completed, the product is collected by centrifugation, washed with ethanol and deionized water three times in sequence, filtered, and the obtained filter cake is vacuum dried at 60°C for 12 h to obtain a white MOFs material UIO-66-OH containing a hydroxyl ligand.

[0031] Example 3

[0032] A method for preparing a UIO-66-CH3 ammonia adsorption material, comprising the following steps: dissolving 1 mmol of ZrCl4 and 1 mmol of 2-methylterephthalic acid in 45 mL of a mixed solvent (formic acid: ethanol: water = 1:3:2), transferring the solution into a polyethylene-lined reaction kettle, heating to 120°C at a rate of 3°C / min and maintaining for 4 hours, and then heating to 150°C at a rate of 3°C / min in the second stage and maintaining for 18 hours. After the reaction is completed, the product is collected by centrifugation, washed with ethanol and deionized water three times in sequence, filtered, and the obtained filter cake is vacuum dried at 60°C for 12 h to obtain a grayish white MOFs material UIO-66-CH3 containing a methyl ligand.

[0033] Example 4

[0034] A method for preparing a UIO-66-CF3 ammonia adsorption material, comprising the following steps: dissolving 1 mmol of ZrCl4 and 1 mmol of 2-trifluoromethylterephthalic acid in 45 mL of a mixed solvent (formic acid: ethanol: water = 1:3:2), transferring the solution into a polyethylene-lined reaction kettle, heating to 120°C at a rate of 3°C / min and maintaining for 4 hours, and then heating to 150°C at a rate of 3°C / min in the second stage and maintaining for 18 hours. After the reaction is completed, the product is collected by centrifugation, washed with ethanol and deionized water three times in sequence, filtered, and the obtained filter cake is vacuum dried at 60°C for 12 h to obtain a MOFs material UIO-66-CF3 containing a trifluoromethyl ligand.

[0035] Comparative Example 1

[0036] A method for preparing a UiO-66-NH2 ammonia adsorbing material, comprising the following steps: 1 mmol of ZrCl4 and 1 mmol of 2-amino terephthalic acid are added to a beaker containing 25 mL of DMF, 25 mL of formic acid is then added, and ultrasonic treatment is performed for 30 min until the solids are completely dissolved; the solution is transferred into a polyethylene-lined kettle, and the temperature is raised to 120°C at a rate of 3°C / min and maintained for 4 h; in the second stage, the temperature is raised to 150°C at a rate of 3°C / min and maintained for 18 h. After the reaction is completed, the temperature is cooled to room temperature, and the product is washed with ethanol and deionized water in sequence after being separated by centrifugation, and then filtered; the filter cake obtained is vacuum dried at 60°C for 12 h to obtain a MOFs material UIO-66-NH2 containing an amino ligand.

[0037] Comparative Example 2

[0038] A method for preparing a UiO-66-NH2 ammonia adsorbing material, comprising the following steps: 1 mmol of ZrCl4 and 1 mmol of 2-amino terephthalic acid are added to a beaker containing 25 mL of DMF, 25 mL of formic acid is then added, and ultrasonic treatment is performed for 30 min until the solids are completely dissolved; the solution is transferred into a polyethylene-lined kettle, and the temperature is raised to 120°C at a rate of 3°C / min and maintained for 4 h; in the second stage, the temperature is raised to 150°C at a rate of 3°C / min and maintained for 18 h. After the reaction is completed, the temperature is cooled to room temperature, and the product is washed with ethanol and deionized water in sequence after being separated by centrifugation, and then filtered; the filter cake obtained is vacuum dried at 60°C for 12 h to obtain a MOFs material UIO-66-NH2 containing an amino ligand.

[0039] Comparative Example 3

[0040] A method for preparing a UiO-66-CH3 ammonia adsorbing material, comprising the following steps: 1 mmol of ZrCl4, 1 mmol of 2-methyl terephthalic acid and 25 mL of formic acid are mixed, and then 25 mL of ethanol is added and ultrasonic treatment is performed for 30 min until the solids are completely dissolved; the solution is transferred into a polyethylene-lined kettle, and the temperature is raised to 120°C at a rate of 3°C / min and maintained for 4 h; in the second stage, the temperature is raised to 150°C at a rate of 3°C / min and maintained for 18 h. After the reaction is completed, the temperature is cooled to room temperature, and the product is washed with ethanol and deionized water in sequence after being separated by centrifugation, and then filtered; the filter cake obtained is vacuum dried at 60°C for 12 h to obtain a MOFs material UIO-66-CH3 containing a methyl ligand.

[0041] Comparative Example 4

[0042] A method for preparing a UiO-66-CH3 amine adsorbing material, comprising the following steps: mixing 1 mmol of ZrCl4, 1 mmol of 2-methylterephthalic acid and 25 mL of formic acid, then adding 25 mL of water and ultrasonicating for 30 min until the solid is completely dissolved, transferring the solution into a polyethylene-lined kettle, heating to 120°C at a rate of 3°C / min and keeping for 4 h, and then heating to 150°C at a rate of 3°C / min in the second stage and keeping for 18 h. After the reaction is completed, cooling to room temperature, separating by centrifugation, and then sequentially washing with ethanol and deionized water, filtering, and drying the obtained filter cake at 60°C under vacuum for 12 h to obtain the MOFs material UIO-66-CH3 containing methyl ligands.

[0043] Comparative Example 5

[0044] A method for preparing a UiO-66-NH2 amine adsorbing material, comprising the following steps: dissolving 1 mmol of ZrCl4 and 1 mmol of 2-amino terephthalic acid in 45 mL of a mixed solvent (formic acid:ethanol:water = 1:3:2), transferring the solution into a polyethylene-lined reaction kettle, and heating to 150°C at a rate of 3°C / min and keeping for 22 h. After the reaction is completed, cooling to room temperature, collecting the product by centrifugation, sequentially washing with ethanol and deionized water for 3 times, filtering, and drying the obtained filter cake at 60°C under vacuum for 12 h to obtain the MOFs material UIO-66-NH2 containing amino ligands.

[0045] Example 1

[0046] The adsorption amount of NH3 of the UiO-66-X group derivative material prepared in the examples and comparative examples was tested for pressure variation at 0-101 kPa, 25°C under an ammonia gas atmosphere with a gas purity of 99.99% by using a Micromeritics 3Flex instrument for static adsorption analysis: first, the mass of an empty sample tube was weighed and recorded, then 0.1 g of the UiO-66-X group derivative material was weighed on a balance, the sample was poured into the bottom of the sample tube using a funnel, the total weight of the sample tube assembly containing the sample was weighed again before degassing at 120°C for 12 h, and the total weight of the sample tube was weighed after the degassing was completed, the weight of the sample after degassing was obtained by subtracting the weight of the empty tube, then the sample tube was installed, the isothermal jacket was installed on the sample tube, the dewar flask was placed, the safety door was closed, and the analysis was waited. The results are shown in Table 1.

[0047] Table 1

[0048] Adsorption capacity (mmol / g) Example 1 (UiO-66-NH2) 11.1 Example 2 (UiO-66-OH) 10.5 Example 3 (UiO-66-CH3) 7.2 Example 4 (UiO-66-CF3) 5.9 Comparative Example 1 8.2 Comparative Example 2 3.6 Comparative Example 3 4.1 Comparative Example 4 3.8 Comparative Example 5 8.2 UiO-66 6.8

[0049] The specific synthesis method of UiO-66 includes: dissolving 1 mmol of ZrCl4 and 1 mmol of terephthalic acid in 45 mL of a mixed solvent (formic acid: ethanol: water = 1:3:2), transferring the solution into a polyethylene-lined reaction kettle, heating to 120 DEG C at a rate of 3 DEG C / min and keeping for 4 hours, and then heating to 150 DEG C at a rate of 3 DEG C / min in the second stage and keeping for 18 hours. After the reaction is completed, the product is collected by centrifugation, washed with ethanol and deionized water in sequence for 3 times, filtered, and the obtained filter cake is dried at 60 DEG C under vacuum for 12 h to obtain a white MOFs material UIO-66 containing a methyl ligand.

[0050] Effect Example 2

[0051] The UiO-66-X group derivative material prepared in Example 1 and the material of Example 1 soaked in water for 30 days are subjected to 6 cycles of adsorption analysis under the following conditions: using a NETZSCH TG 209F1 Libra instrument, under an atmosphere of 20% ammonia gas (gas cylinder: 20% ammonia gas + 80% nitrogen gas), at an ammonia gas flow rate of 10 mL / min, at a low pressure of 0.16 bar and a room temperature of 40 DEG C, the test material is activated at 120 DEG C under vacuum for 12 h, then 10 mg of the activated material is placed in a 3 mL NETZSCH TG 209F1 Libra instrument small crucible, and the adsorption is carried out at 0.16 bar and 40 DEG C with an ammonia gas flow rate of 10 mL / min, after the adsorption reaches saturation, desorption is carried out at 80 DEG C, and the same conditions are repeated for 6 times, and the results are shown in Table 2 and Figure 2 .

[0052] Compared with the UiO-66-X group derivative material (UiO-66-NH2) without water treatment, the material soaked in water for 30 days (UiO-66-NH2) has only a slight decrease in adsorption capacity, the structural integrity retention rate is > 99%, and during the cyclic adsorption process, efficient desorption can be achieved at 80 DEG C. It is proved that the water stability is high and the cyclic use performance is superior, and it can be recycled and reused.

[0053] The specific surface area of the UiO-66-X material prepared by the application for ammonia adsorption is as high as 1100 m 2 / g or more, and has good acid strength and density, which is beneficial to the adsorption of ammonia gas.

[0054] Table 2

[0055]

[0056] Effect Example 3

[0057] The UiO-66-X group derivative materials prepared in Examples 1-3 and UiO-66 were characterized by a Nicolet (Thermo Fisher) Nicolet iS10 Fourier transform infrared spectrometer: about 1-2 mg of sample powder was weighed, mixed with about 100 mg of dry KBr, and pressed into a transparent round sheet by a mold, and the scanning range was set to 4000-400 cm -1 , the resolution was 4 cm -1 , the scanning times were 16 to improve the signal-to-noise ratio. The background spectrum of pure KBr was first measured to correct the instrument noise and background absorption, and then the test was started after placing the sample, and the transmittance spectrum was recorded as a function of the wave number. The results are shown in Figure 3 .

[0058] The wave number 806 cm -1 nearby of UiO-66 is attributed to Zr-O stretching vibration or characteristic peak of benzene ring substituent, 1657 cm -1 is C=O stretching vibration, derived from terephthalic acid ligand (BDC). Compared with UiO-66, the enhancement of UiO-66-NH2 at 1657 cm -1 is the coupling vibration of C=O and NH2. The symmetric and asymmetric stretching vibration of NH2 at 3500-3300 cm -1 . The introduction of -NH2 causes more peaks in the low wave number region (600-1600 cm -1 ), indicating that the internal vibration mode of the molecule is more complex. UiO-66-OH appears characteristic peaks of OH stretching vibration at 3200-3600 cm -1 , and 1657 cm -1 indicates that the hydroxyl group participates in hydrogen bond formation, and the introduction of -OH enhances the peak shape in the low wave number (1000 cm -1 ) region. The absorption peak of UiO-66-CH3 at 2969 cm -1 is significantly enhanced, which is the C-H asymmetric stretching vibration of -CH3 group, and compared with other modifications, it has less effect on the low wave number region (600-1600 cm -1 ), indicating that CH3 has less disturbance to the MOF framework, and the 1657 cm -1 peak is still retained, indicating that the modification method does not change the carboxyl skeleton structure of the ligand.

[0059] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present application and not to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present application.

Claims

1. A method for preparing a UiO-66-X ammonia adsorption material, characterized in that: The zirconium salt and the organic ligand are mixed and then added to a ternary solvent of formic acid, ethanol and water for a hydrothermal reaction. After the reaction is completed, the mixture is cooled to room temperature, separated, washed and dried to obtain a UiO-66-X material for ammonia adsorption.

2. The method for preparing the UiO-66-X ammonia adsorption material according to claim 1, wherein: The zirconium salt is one of zirconium tetrachloride, zirconium oxychloride octahydrate, zirconium oxynitrate hydrate, zirconium tetraacetate, and zirconium acetate hydrate.

3. The method for preparing the UiO-66-X ammonia adsorption material according to claim 1, wherein: The organic ligand is one of 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2-methylterephthalic acid, 2-trifluoromethylterephthalic acid, 2-chloroterephthalic acid, 2-fluoroterephthalic acid, 2-bromoterephthalic acid, 2-iodoterephthalic acid, 2,5-dichloroterephthalic acid, 2,6-dichloroterephthalic acid, 2,5-difluoroterephthalic acid, 2,3-difluoroterephthalic acid, tetrafluoroterephthalic acid, 2-bromo-5-fluorobenzoic acid, 2,5-dibromoterephthalic acid, tetrabromoterephthalic acid, 2,5-dihydroxyterephthalic acid, and 2,5-diiodoterephthalic acid.

4. The method for preparing the UiO-66-X ammonia adsorption material according to claim 1, wherein: The temperature of the hydrothermal reaction is 120-150° C., the time is 20-24 h, and the gradient heating rate is 2-5° C. / min.

5. The method for preparing the UiO-66-X ammonia adsorption material according to claim 4, characterized in that: The hydrothermal reaction adopts staged temperature control, specifically: in the first stage, the temperature is raised to 120° C. and maintained for 4 hours, and in the second stage, the temperature is raised to 150° C. at 3° C. / min and maintained for 18 hours.

6. The method for preparing the UiO-66-X ammonia adsorption material according to claim 1, wherein: The molar ratio of the zirconium salt to the organic ligand is 1:(0.8-1.2).

7. The method for preparing the UiO-66-X ammonia adsorption material according to claim 1, wherein: The molar ratio of the zirconium salt to formic acid is 1:(1-2).

8. The method for preparing the UiO-66-X ammonia adsorption material according to claim 1, wherein: The volume ratio of formic acid, ethanol and water is 1:(2-4):(2-3).

9. The UiO-66-X material prepared by the method for preparing the UiO-66-X ammonia adsorption material according to any one of claims 1 to 8 has a chemical formula of Zr6O4(OH)4(X) 6-n (COOH) n , wherein X is a terephthalic acid derivative, and n=1-3.

10. Use of the UiO-66-X material according to claim 9 in NH3 adsorption.